Advertising in digital applications and mobile games as a monetization element - Bobrov, V. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2024)
The paper explores the specifics of the term "monetization" for video games and examines similar monetization systems for non-gaming platforms. It reviews the dynamics of the video game market as a whole, particularly the mobile game market, and analyzes the current state of the mobile gaming market. The stages of market formation and the evolution of digital goods are presented in chronological order, using video games as an example, along with the evolution of advertising integrations from the 1990s to the present day. Examples of advertising usage before the widespread adoption of mobile devices and connectivity are provided, such as product placement and DLC. The characteristic features of different sales systems are defined: Free-to-play, Freemium, Pay-to-play. Their advantages and distinctive monetization features are outlined, and the reasons for the dominance of Free-to-play and Freemium in the current mobile gaming market are identified. The work offers a detailed characterization of the main types of video advertising in mobile games: native advertising, video advertising, rewarded video ads, demos, and contextual advertising. The reasons for the proliferation of each type of advertising are revealed, and the main advantages and challenges of using video advertising, in general, are identified for both advertisers and publishers. Examples from modern mobile games and applications are systematized depending on the advertiser, the game distribution model, and the complexity of implementation. Specialized monetization elements specific to certain types of video advertising are examined. The research results can be used to build a monetization strategy for developing freemium and free-to-play gaming or entertainment projects, to assess the appropriateness of using video games as a platform for placing one's advertising, or to predict user behavior from the perspective of the experience economy and interaction with digital goods.